Formulation, characterization, antioxidant and sun protection factor activity of red pomegranate (Punica granatum l.) peel extract in sunscreen lotion - Faizatun, Faizatun; Tanoto, Vingko; Maharani, Syifa Caroline (Journal of Natural Product for Degenerative Diseases, 2025)
Red pomegranate (Punica granatum L.) contains phenolic compounds of elagic acid as antioxidants and flavonoids and tannins as sunscreens in protecting the skin against ultra violet radiation. The aim of this study was to determine the sunscreen and antioxidant activity of red pomegranate peel extract, also the formation of its stable sunscreen lotion and to determine its SPF and antioxidant activity. Red pomegranate peel was macerated with 70% ethanol and concentrated. Antioxidant activity testing using FRAP method and determination of SPF value, spectrophotometric method was used along with Mansur equation. Lotion formulation was done by adding red pomegranate peel extract as much as 0.06% (F1); 0.12% and 0.24% (F2). The lotion preparation was evaluated for physical and chemical parameters including organoleptic, homogeneity, viscosity and flow properties, lotion type, pH, spreadability, determination of SPF value and stability test using freeze and thaw method. The results showed the IC50 value of red pomegranate peel extract was 12.42 ± 0.01 bpj and the value of sunscreen activity at a concentration of 400 bpj gave an SPF value of 25.91 ± 0.01. The result of testing the physical properties showed that the lotion type was o/w, viscosity ranges from 10400 to 12000 cPs, pH test from 7.25 to 7.60, spreading power from 6.31 to 6.42 cm. The lotion was stable as there was no phase separation observed after centrifugation, freeze-thaw and thermal stress tests. For the lotion of red pomegranate peel extract showed antioxidant activity with IC50 values of 98.73 bpj (F1); 68.89 bpj (F2); 48.30 bpj (F3) and sunscreen values of 13.11 ± 0.02 (F1); 20.78 ± 0.02; 24.78 ± 0.04. It can be concluded that red pomegranate peel extract has very strong antioxidant activity and sunscreen activity with moderate protection, and can be formulated into lotion preparations with good quality parameters.